(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Over the last decades, long term treatment with metformin has been recognized as a possible cause of alterations in serum B12 and folic acid value of type 2 diabetic patients. Metformin can affect the absorption of vitamin B12 and folic acid which ultimately results in neurological and hematological complications has been designed to assess serum vitamin B12 and folic acid status of type II diabetic patients on metformin. Materials and methods: This hospital based cross sectional study was conducted in Department of Physiology, Chittagong Medical College in collaboration with Department of Medicine and Department of Endocrinology, Chittagong Medical College Hospital from July 2021 to June 2022. Total 70 diagnosed type 2 diabetic patients were included in the study among which 35 patients aged between 45-55 years and on metformin therapy for more than 2 years were taken as case group and in control group age and sex matched 35 diagnosed diabetic patients not treated with metformin were included. Serum vitamin B12 and folic acid were measured in all patients. Collected data was analyzed by SPSS-26. Results: Values of serum vitamin B12 were significantly lower in metformin exposed diabetic patients compared to metformin unexposed patients (p<0.001). Folic acid levels of metformin exposed diabetic patients were also decreased but it was not statistically significant (p>0.05). Duration and dose of metformin had significant negative correlation with vitamin B12 level. But serum folic acid levels were not correlated with dose and duration of metformin use. Conclusion: The results of this study concludes that long term use of metformin can alter vitamin B12 and folic acid level in type 2 diabetic patients. Chatt Maa Shi Hosp Med Coll J; Vol.24 (1); Jan 2025; Page 12-16